2021
DOI: 10.3389/fped.2021.678937
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms, SARS-CoV-2 Antibodies, and Neutralization Capacity in a Cross Sectional-Population of German Children

Abstract: Background: Children and youth are affected rather mildly in the acute phase of COVID-19 and thus, SARS-CoV-2 infection infection may easily be overlooked. In the light of current discussions on the vaccinations of children it seems necessary to better identify children who are immune against SARS-CoV-2 due to a previous infection and to better understand COVID-19 related immune reactions in children.Methods: In a cross-sectional design, children aged 1–17 were recruited through primary care pediatricians for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…We also included serum samples negative for SARS-CoV-2 antibodies from healthy paediatric control patients, referred to as healthy controls herein, and serum samples from children with a history of asymptomatic or mild COVID-19, from the CoKiBa study. 29 Healthy controls were age and sex-matched with the MIS-C group (multiple matched cases for each MIS-C group). Samples in the CoKiBa study were obtained 1–3 months after the peak of the first pandemic wave (spring 2020) in Bavaria.…”
Section: Methodsmentioning
confidence: 99%
“…We also included serum samples negative for SARS-CoV-2 antibodies from healthy paediatric control patients, referred to as healthy controls herein, and serum samples from children with a history of asymptomatic or mild COVID-19, from the CoKiBa study. 29 Healthy controls were age and sex-matched with the MIS-C group (multiple matched cases for each MIS-C group). Samples in the CoKiBa study were obtained 1–3 months after the peak of the first pandemic wave (spring 2020) in Bavaria.…”
Section: Methodsmentioning
confidence: 99%
“…However, it also could not be excluded that other (adult) family members were the source of the infection in the family, as shown in previous studies from the first SARS-CoV-2 wave in spring of 2020. 8 To protect schools from uncontrolled SARS-CoV-2 transmissions, pool PCR screening was recommended to be implemented at a low initial incidence, at much lower incidence rates as reported here, as the effects of pool PCR screening were suspected to lose power as incidence increases. 9 However, we found that the protective effect of the screening does not only depend on incidence but also on the logistics of the testing setup.…”
Section: Discussionmentioning
confidence: 88%
“…При этом у 86% из них развивалась достаточная нейтрализующая активность независимо от возраста и пола. Приблизительно у 30% ПЦР-позитивных детей сероконверсия не наблюдалась [30]. В Соединенных Штатах среди 1038 детей исследователи обнаружили антитела IgG против SARS-CoV-2 в 8,5% случаев, притом что у 66% серопозитивных детей не было симптомов COVID-19 ни в анамнезе, ни на момент обследования.…”
Section: почему у детей Covid-19 протекает в более легкой форме?unclassified